Implications of Missed Care, Nurse Staffing, and the Nursing Work Environment on Patient Outcomes in Maternity, Neonatal, and Pediatric Inpatient Settings. Issue 5 (September 2020) - Simpson, Kathleen Rice
Abstract : In this special topics series on maternity, neonatal, and pediatric nurse staffing and the nursing work environment, we present four studies that cover challenges of practicing in stressful clinical settings including inadequate nurse staffing and unsafe environments, relative to potential implications for patients and nurses. Missed, delayed, and incomplete nursing care is now being studied in these specialty settings with a focus on links to patient outcomes. Two of the studies specifically included hospitals' adherence to the Association of Women's Health, Obstetric, and Neonatal Nurses nurse staffing guidelines as a factor in their findings and clinical implications.